Role of Rab10 in cocaine-induced behavioral effects is associated with GABAB receptor membrane expression in the nucleus accumbens - Yu, Zhuoxuan; Fu, Qiang; Qiu, Tianyun; Yang, Caidi; Lu, Mingfen; Peng, Qinghua; Yang, Jianhua; Hu, Zhenzhen (Frontiers in Pharmacology, 2024)
Aims: Previous studies have demonstrated that Ras-related GTP-binding protein Rab10 (Rab10) participates in psychostimulant-induced behavioral effects. Here, we showed that Rab10 in the nucleus accumbens (NAc) of male animals affects the development of cocaine-induced behavioral effects, which are associated with the plasma membrane expression of GABAB heteroreceptor (GABABR). Methods: We performed flow cytometry, immunoendocytosis, pHluorin activity analysis, electrophysiology analysis, and open field test to explore the role of Rab10 in modulating the membrane expression and function of GABABR, as well as its regulatory effect on cocaine-induced behavioral effects. Results: Transcriptomics analysis showed that Rab10 was elevated by acute cocaine treatment. Membrane levels of Rab10 increased within day 1 of the cocaine treatment, subsequently decreased in following timepoints. Rab10 deficiency in NAc regions significantly increased cocaine-inhibited membrane GABABR levels and inhibited cocaine-induced hyperlocomotion and behavioral sensitization. In addition, GAD67+ neurons from NAc regions treated with cocaine revealed significantly decreased Rab10 membrane expression. Furthermore, NAc neurons-specific Rab10 knockout resulted in a significant increase in the cocaine-inhibited membrane expression of GABABR, together with increases in mIPSCs amplitude and attenuation of baclofen-amplified Ca2+ influx. Conclusion: These results uncover a new mechanism by which Rab10-GABABR signaling can be a potential mechanism for regulating cocaine-induced behavioral effects.